2015
DOI: 10.1371/journal.pgen.1005242
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 9 Regulation by MicroRNAs Controls Lung Development and Links DICER1 Loss to the Pathogenesis of Pleuropulmonary Blastoma

Abstract: Pleuropulmonary Blastoma (PPB) is the primary neoplastic manifestation of a pediatric cancer predisposition syndrome that is associated with several diseases including cystic nephroma, Wilms tumor, neuroblastoma, rhabdomyosarcoma, medulloblastoma, and ovarian Sertoli-Leydig cell tumor. The primary pathology of PPB, epithelial cysts with stromal hyperplasia and risk for progression to a complex primitive sarcoma, is associated with familial heterozygosity and lesion-associated epithelial loss-of-heterozygosity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 66 publications
3
33
0
Order By: Relevance
“…Fgf9 overexpression in lung epithelium induces epithelial branching arrest and luminal dilation in combination with decreased and increased Shh and Fgf10 expression, respectively (White et al, 2006). Recently, augmented Fgf9 expression was reported in the lung epithelium of E12.5 Dicer (Yin et al, 2015). Our results indicated that Fgf9 expression was not affected in lungs from E14.5 Dicer mutants, whereas it was reduced in Yy1 mutant specimens.…”
Section: Discussionsupporting
confidence: 43%
“…Fgf9 overexpression in lung epithelium induces epithelial branching arrest and luminal dilation in combination with decreased and increased Shh and Fgf10 expression, respectively (White et al, 2006). Recently, augmented Fgf9 expression was reported in the lung epithelium of E12.5 Dicer (Yin et al, 2015). Our results indicated that Fgf9 expression was not affected in lungs from E14.5 Dicer mutants, whereas it was reduced in Yy1 mutant specimens.…”
Section: Discussionsupporting
confidence: 43%
“…It's reported that FGF9 mRNA high expression was correlated with poor survival [10]. Moreover, miRNA-FGF9 pathway is important for lung development and regarded as an initiating factor for pleuropulmonary blastoma [25]. Induction of FGF9 in adult lung can lead to the rapid formation of epithelial tumours [26].…”
Section: Discussionmentioning
confidence: 99%
“…2 Genes implicated in CPAM, PPB and BAC [14,30,31,32,33,34,35,127,137,138,139,140,141,142,143]. TTF1 = Thyroid transcription factor 1; PDGF-B = platelet-derived growth factor B; FABP-7 = fatty acid-binding protein 7; GDNF = glial cell-derived neurotrophic factor; Shh = sonic hedgehog; FGFR2b = FGF receptor-2b; FHIT = fragile histidine triad; Rb = retinoblastoma protein; EGFR = epidermal growth factor receptor. …”
Section: Managementmentioning
confidence: 99%